Crocin attenuates osteoclastogenesis and enhances bone health by skewing the immunoporotic "Treg-Th17" cell axis in post-menopausal osteoporotic mice model - Zaffar Azam; Leena Sapra; Asha Bhardwaj; Sumedha Yadav; Pradyumna K. Mishra; Prashant Shukla; Versha Sharma; Rupesh K. Srivastava (Elsevier, 2022)
Background: Crocin is a well-known carotenoid with established anti-inflammatory, anti-arthritic, anti-tumor, and antioxidant properties. Previous studies have also identified crocin as a potential drug candidate for osteoporosis treatment; however, the mechanisms underlying its direct influence on the host osteo-immune system is unexplored.Hypothesis: In the present study we presume that crocin may enhance bone health via modulating the host osteo-immune system in post-menopausal osteoporotic mice model.Study design and methods: The present study delineates the osteoprotective potential of crocin both under in vitro as well as under in vivo (ovariectomized-Ovx mice model) conditions. For in vitro studies, osteoclast differentiation and functional activity was performed on mice bone marrow cells in osteoclastogenic media supplemented with M-CSF (30 ng/ml) and RANKL (100 ng/ml) in the presence or absence of crocin at different concentrations (10, 50 and 100 µM). For in vivo study, we randomly allocated 8-10 weeks old female Balb/c mice into three groups (Sham, Ovx, and Ovx+crocin). Ovx+crocin group animals were orally administered with crocin (50 mg/kg/day) for 45 days. At the end of experiment, mice were sacrificed and analysis of various osteo-immune parameters was performed for investigating the anti-osteoporotic activity of crocin via various cutting-edge techniques i.e., Scanning Electron Microscopy (SEM), Micro-computed tomography (µ-CT), Flow cytometry, and Enzyme-Linked Immunosorbent Assay (ELISA).Results: From the in vitro studies, it was observed that crocin significantly reduced RANKL induced osteoclastogenesis along with inhibiting the functional activity of osteoclasts in a dose dependent manner in mouse bone marrow cells. Moreover, our in vivo data (µ-CT and Flow cytometry) suggested that crocin administration enhances bone health via significantly enhancing the percentage of anti-osteoclastogenic regulatory T cells (Tregs) along with significantly reducing osteoclastogenic Th17 cells in comparison to control group. Immunomodulatory potential of crocin was further confirmed from serum cytokine data where it was observed that there is a significant enhancement in the level of anti-osteoclastogenic interleukin (IL)-10 cytokine along with simultaneous reduction in the levels of osteoclastogenic cytokines such as IL-6, TNF-α, IFN-γ and IL-17.Conclusion: Altogether, the present study for the first time establishes the immunological & cellular mechanisms for crocin mediated enhanced bone health in Ovx induced post-menopausal osteoporotic mice model.